Analisis Pemilihan Moda Transportasi Penumpang Antara Bus Dan Kereta Api Rute Purwodadi - Semarang - Pujiyanto, Teguh; , Nurul Hidayati, ST.,MT.,Ph.D (2017)
Modes choice of transportation to trevel is influenced by many factors, including the condition of public transport services. It is also a consideration in Purwodadi City community to select the mode of transportation. This study aims to determine the characteristics of respondents as users of public transport, travel characteristics and create a model of modal choice in Purwodadi. Characteristics of the traveling in cluded: modal choice, gender, age, and occupation, while the characteristics of the trip consists of: cost, destination, travel time, and the reason for choosing a mode of transportation. Analysis of modal choice is based on the binary logit model differences and ratios. The result of analysis show that: 63% of respondents choose to use the train, gender is dominated by men (51,7%), with ages between 31-40 years (36,3%) and worked as self employed (64,8%). In addition, mayority of respondents spend traveling cost Rp 40,000-Rp 60,000 (45.7%), aimed to Semarang (91,1%), with a long trip around 90-120 minutes (43,3%), 54% chose bus because of the safety factor, and 43,5% chose the train because of the speed factor. The obtained modal choice model are: P1= 1/(1+